Analysis of Indonesian maritime management and threats to marine security - Puguh Toko Arisanto; Aldaneva Reisika Jenny Alviany; Audry Sitoresmi Leilani; Anggie Chyntia Amanda Putri (The International Journal of Politics and Sociology Research, 2023)
Indonesia has many opportunities and challenges as a country with a strong maritime character. Greater attention is needed to the sea area. However, various problems and obstacles must be overcome. This research used a qualitative descriptive method, which refers to secondary data obtained from books, journal articles, and online sources. The theory of maritime security and sea power concept is used to analyze the data. In this case, the Government of Indonesia has issued a World Maritime Axis policy as a basis for developing marine management in Indonesia. In addition, the authors also suggest integration between security agencies, maritime diplomacy, sustainable fisheries management, and increasing human resources to improve marine management in Indonesia.